2001
DOI: 10.1006/viro.2000.0847
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Beak and Feather Disease Virus Detected in Psittacine Species in Australia

Abstract: The complete nucleotide (nt) sequence of eight isolates of beak and feather disease virus (BFDV) obtained from a range of psittacine species with psittacine beak and feather disease (PBFD) from throughout Australia were compared with the sequences of two BFDV isolates previously reported from Australia (BFDV-AUS) and America (BFDV-USA), respectively. All isolates had the same basic structure including the position of the open reading frames, the hairpin structure between ORF1 and ORF2, the nonanucleotide motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 27 publications
2
76
0
1
Order By: Relevance
“…We observed that the viral sequences of strains that produce the peracute illness clustered closely with the strains responsible for the chronic disease, thus suggesting the absence of a specific BFDV genetic variant accountable for a specific form of PBFD, as formerly hypothesized (Ypelaar et al, 1999;Bassami et al, 2001;Heath et al, 2004;Raue et al, 2004;Hughes & Piontkivska, 2008). On the basis of this observation, we have hypothesized that the clinical and pathological differences between aPF and CF of the disease could be strictly related to the age and host immune system status, rather than genomic differences between viral strains.…”
Section: Discussionmentioning
confidence: 52%
“…We observed that the viral sequences of strains that produce the peracute illness clustered closely with the strains responsible for the chronic disease, thus suggesting the absence of a specific BFDV genetic variant accountable for a specific form of PBFD, as formerly hypothesized (Ypelaar et al, 1999;Bassami et al, 2001;Heath et al, 2004;Raue et al, 2004;Hughes & Piontkivska, 2008). On the basis of this observation, we have hypothesized that the clinical and pathological differences between aPF and CF of the disease could be strictly related to the age and host immune system status, rather than genomic differences between viral strains.…”
Section: Discussionmentioning
confidence: 52%
“…The clustering among these viruses indicates a possible association between the viruses and their host species (Bassami et al, 2001;Ritchie et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Virus detection in live birds can be achieved by haemagglutination using erythrocytes from goffin cockatoos, guinea pigs or galahs (Ritchie et al, 1991;Raidal et al, 1993). The determination of the complete nucleotide sequence of BFDV was the basis for establishment of molecular detection methods, especially polymerase chain reaction (PCR) (Ritchie et al, 1989;Bassami et al, 1998Bassami et al, , 2001. Ypelaar et al (1999) tested several primer combinations that hybridized with various regions of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is considered a significant conservation threat and has been implicated in parrot declines in Australia and globally (27)(28)(29)(30). BFDV possesses a single-stranded DNA genome of ∼2,000 nucleotides (31). Like most small single-stranded DNA and RNA viruses, BFDV shows high levels of genetic variation and recombination (27,32,33), and evolves rapidly in novel conditions (34), with multiple variant infections present in individual animals (29).…”
Section: Significancementioning
confidence: 99%